Perlindungan Hukum Terhadap Pegawai Pengelola Anggaran Atas Kesalahan Administrasi Yang Menyebabkan Kerugian Negara (Studi Pada Dinas Ketahanan Pangan, Tanaman Pangan Dan Hortikultura Provinsi Sumatera Utara) - Husna, Wardatul; Sahbudi, Sahbudi; Arif, Zuhri (Universitas Medan Area, 2025)
The background of this research is based on the many cases of state losses arising from administrative errors by employees, which are often not based on intent, but have the potential to result in criminal sanctions. The purpose of this research is to determine the form of legal protection for budget management employees who commit administrative errors, analyze the mechanism for resolving state losses, and examine the efforts of the Food Security, Food Crops and Horticulture Service of North Sumatra Province in preventing administrative errors. This research uses an empirical juridical method with a statutory approach and a case approach, through literature studies, observations, and interviews with relevant sources. The results show that legal protection for budget management employees is provided through the principle of **ultimum remedium**, the principle of presumption of innocence, and the provisions of Law Number 30 of 2014 concerning State Administration. The mechanism for resolving state losses prioritizes administrative channels and claims for compensation (TP-TGR), while criminal channels are only taken if there is evidence of abuse of authority or malicious intent. The North Sumatra Food Security, Food Crops, and Horticulture Agency is working to improve employee competency through training, implementing a government internal control system (SPIP), and implementing multi-layered oversight to minimize administrative errors.